Aphasia and dysarthria in acute stroke: recovery and functional outcome. Issue 3 (6th November 2013) - Ali, Myzoon; Lyden, Patrick; Brady, Marian; ,
Abstract : Background: Aphasia and dysarthria have major implications for activities of daily living and social participation following stroke. Few studies describe recovery in the acute stroke setting. We described the evolution of aphasia and dysarthria by three‐months poststroke. Methods: We conducted a retrospective analysis of pooled clinical trial data from the Virtual International Stroke Trials Archive. We defined aphasia and dysarthria at baseline as a score of ≥1 on the Best Language (Item 9) and Dysarthria (Item 10) domains of the National Institutes of Health Stroke Scale, respectively. We described recovery from these impairments by three‐months. Covariate adjusted analyses described the associations between aphasia, dysarthria, and functional outcome using the modified Rankin Scale at three‐months following stroke. Results: At baseline, 4039/8904 (45·4%) people presented with aphasia and 6192 (69·5%) with dysarthria; 2639 (29·6%) had both impairments. By three–months, aphasia and dysarthria had resolved in 1292/7219 (17·9%) and 2892/7219 (40·1%) survivors, respectively, but persisted in 1713/7219 (23·7%) and 1940/7219 (27%), respectively. Age and severity of initial stroke were associated with poor recovery, whereas thrombolysis was associated with improved recovery. Aphasia at baseline [ P = 0·049, odds ratio = 0·89, 95% confidence interval (0·79, 1·00)] and persistent aphasia at three‐months [ P < 0·0001, odds ratio = 0·31, 95% confidence interval (0·27, 0·35)] were each associated with poorer modified Rankin Scale scores at three‐months. Conclusion: Aphasia or dysarthria persisted in at least a quarter of people in our dataset at three‐months following stroke. The association between persistent aphasia at three‐months and poor modified Rankin Scale renders this impairment a major therapeutic target for recovery and restitution.